Influence of Different Refrigerants on Motor Cooling Process and System Performance of Compressor with Gas Bearings - Liu Yiteng; Gao Yiming; Liu Guangbin; Song Junnan; Gong Jieming (Zhileng xuebao)
Motor cooling is key to the reliable operation of centrifugal refrigeration compressors with gas bearings. A mathematical model of a centrifugal refrigeration compressor with gas bearings was devised, and the influences of different refrigerants on the motor cooling process and refrigeration system performance were analyzed. The results show that the internal temperature of the motor reaches the highest when R1234ze (E) is used, and the maximum temperature of the permanent magnet of the motor is 60–90 °C higher than that with R134a and R1234yf. When using the three refrigerants, the average winding temperature of the motor decreases with an increase in the cooling inlet temperature. When R134a and R1234yf are used, the maximum temperature of the permanent magnet decreases with an increase in the cooling inlet temperature. When R1234ze (E) is used, the maximum temperature of the permanent magnet first increases and then decreases with the increase in cooling inlet temperature. The maximum temperature is reached when the cooling inlet temperature is approximately 25 ℃. The outlet vapor quality of the motor cooling circuit decreases by approximately 3%–5% when the cooling inlet temperature increases by 4.5 °C. Compared with traditional systems, systems with motor cooling branches can control the motor temperature within a safer operating range. However, systems using R134a, R1234yf, and R1234ze (E) have COPs reduced by 1.23%–1.82%, 1.23%–1.65%, and 1.14%–1.17%, respectively.